Rare bird documentation form for Greater Scaup at Hoosier Creek in 1979 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1979)
Rare bird documentation form for three Greater Scaups at Hoosier Creek in Johnson County, IA on April 7, 1979. Epson - sheet feed